Getting intentional about M&E: choosing suitable approaches for adaptive programmes - Management, Global Learning for Adaptive (GLAM Blog, 2020)
Does the choice of monitoring and evaluation (M&E) approaches and tools matter for adaptive programmes? In short, yes: monitoring, evaluation and learning (MEL) and adaptive management (AM) are intertwined. While programme monitoring data and evaluation results are not the only sources of evidence that programmes use for learning and iteration, they often are amongst most important ones — or at least they should be. Selecting what type of information to collect and analyse — and how — is critical for any type of programme. However, what AM especially focuses on is intentionally building in opportunities for structured and collective reflection, ongoing and real-time learning, course correction and decision-making in order to improve effectiveness.

Adaptive management: A practical guide to mitigating uncertainty and advancing evidence-based programming - Byom, K.; Ingram, M.; Oakley, A.; Serpe, L. (PACT, 2020)
Pact’s Adaptive Management Guide provides practical guidance to development practitioners globally on the mindsets, behaviors, resources, and processes that underpin an effective adaptive management system. It presents an approach to managing adaptively that is rooted in complexity analysis and program theory. It draws on Pact’s global experiences and work on topics as diverse as health, livelihoods, markets, governance, capacity development, women and youth, and more. This document begins with an introduction to adaptive management, then walks through successive steps to determine how much adaptation a project requires and how to design an appropriate system. The second half of this guidebook contains a toolkit of examples and templates that projects can tailor to their needs.

Project facilitation as an active response to tensions in international development programmes - Lannon, John; Walsh, John N. (International Journal of Project Management, 2020)
This paper examines the tension within international development programmes between traditional task-oriented approaches to development and the wider view of programmes as sites for adaptability and learning. It characterises it as a set of inter-related tensions between recursive and adaptive tendencies that exist at individual actor, programme and institutional levels. Drawing on a multiple interpretive case study of partnership based programmes between an international non-government organisation and local partners in three countries, it looks at how these tensions play out in practice. Based on the findings, it proposes an active response to the tensions called project facilitation. This is an adaptive and co-created process that incorporates local experience and practice based knowledge to achieve strategic goals, while utilising recognised project management practices to achieve agreed outcomes. By adopting active responses to the tensions that exist within programmes it offers greater potential for effective delivery of long term benefits than the more typical defensive response strategies. Project facilitation is consistent with the social constructionist view of programmes and programme management but broadens our understanding by emphasising the need to actively consider how the tensions inherent in programmes are responded to.
Keywords: Adaptive management; International development; Non-governmental organisations; Partnership; Programme management; Project facilitation; Tensions

Reacting or adapting? Purposeful adaptation and response to contextual change. - Wood, Nik (Rebel with Causation, 2020)
Adaptive management is increasingly on the ticket for development programming, and has been crucial in the wake of covid-19. I’ve been working with adaptive programmes for most of my career, …

Linking constituent engagement and adaptive management - Buell, Stephanie; Campbell, Megan; Pett, Jamie (Overseas Development Institute, 2020)
Constituent engagement is the two-way process of involving constituents in the design, delivery, monitoring and evaluation of programmes. Constituent engagement and adaptive management together can be a powerful combination; high-quality constituent engagement can reinforce effective adaptive management, and vice versa. By highlighting stories from leading practitioners and their organisations, this paper explores how programmes ensure that constituent engagement informs meaningful adaptation. Key messages Constituent engagement and adaptive management are both important tools for implementing responsive and effective development programmes. Together, they can be a powerful combination: input from constituent engagement can be a key source of information and evidence that meaningfully informs programme design and adaptation, and closing the feedback loop in this way increases the quality of future engagement. Both adaptive management and community engagement principles recognise that, for a programme to be effective, it must be responsive to the people meant to ultimately benefit from it. Beyond providing a key source of information for potential programme adaptations, constituent engagement efforts also help build trust with stakeholders, align expectations and promote accountability. This paper explores five key elements for ensuring that constituent engagement and adaptive management are effectively linked within a programme: strong internal systems and external channels; skilled staff that value engagement and adaptation; decision-maker champions; clear points for reflection and action; and a meaningful role for constituents.

Adapting data collection and utilisation to a Covid-19 reality: Monitoring, evaluation and learning approaches for adaptive management - Ziegler, Jessica; Mason, Paige (Briefing Paper, 2020)
This briefing note focuses on the remote collection and use of data for adaptive management during the Covid-19 pandemic, setting out key considerations to help practitioners think through a transition from more ‘traditional’ monitoring, evaluation and learning (MEL) to MEL for adaptive management (MEL4AM) that reflects the unique data collection challenges presented by Covid-19. The brief provides an overview of some key considerations in remote data collection, when this is required, and identifies other sources that address these issues in more detail. It concludes with a discussion of how to bring the information resulting from remote monitoring into decision-making to enable adaptive management. Key messages - When planning for remote data collection during the Covid-19 pandemic, first determine what information is still necessary, because data needs may have changed, e.g. if programming has pivoted or needs to pivot due to Covid-19. Then identify how the programme’s information needs align with existing data sources and what gaps remain, which will guide the need for remote data collection. - Also consider what data is ‘good enough’ for current decision-making needs in order to provide sufficient information to the right people at the right time to an acceptable standard of rigour. - There may be pragmatic reasons to reduce the number or scope of MEL activities, such as logistical constraints or ethical considerations introduced by the pandemic. - MEL activities should be accompanied by frequent feedback loops and pause points to reflect on emergent needs and challenges, information needs that have been met, and contextual changes that may affect MEL. - Be clear with decision-makers about the assumptions and gaps in the data, including proxies used and their limitations, sampling changes, and how these changes and assumptions may affect the decisions/options being discussed.

Contribution analysis for adaptive management - Apgar, Marina; Hernandez, Kevin; Ton, Giel (Briefing Paper, 2020)
This briefing note shares practical learning on the use of contribution analysis for adaptive management (CA4AM). It examines how the approach enables programmes to work with theories of change in a practical, reflexive way, and how, combined with assessing evidence of a programme’s contribution to change, its findings can inform programme adaptation. It also examines both how and to what extent CA enables AM through the experiences of four large complex programmes all working towards systems-level change and employing a structured process of reflection on theories of change. Key messages CA4AM can enable programmes to work with theories of change in a practical, reflexive way. It is particularly useful for programmes operating in conditions of complexity, when it is difficult to discern attribution and when systems-level change is the goal. A range of enabling factors help CA4AM to be used most effectively, including contractual flexibility; embedded monitoring, evaluation and learning (MEL); and supportive leadership.

Listen carefully. Tread lightly. Adapt quickly. Approaching Adaptive Management: Examples from our Somalia Education Programming - CARE (CARE Learning, 2020)
Adaptive management approaches potentially offer us opportunities to deliver high quality results in circumstances where change is complex, including in fragile, unstable or conflict affected places. However, building adaptive programming continues to be a challenge for the sector. For CARE, our Department for International Development -UK Aid funded Girls’ Education Challenge (GEC) programming has provided useful learning on how to operationalise adaptive approaches. In this paper we expand on our learning from this project and offer some recommendations for how to create more opportunities for truly adaptive programming in the future. In particular: • Projects that are designed to adapt need budget structures, results frameworks and governance that enable the process of adaptation. In our GEC projects the approaches employed by DFID, including the introduction of Review and Adaptation meetings have served to support meaningful adaptation. • Adaptive projects require both strong participatory elements and flexible governance and accountability structures. Whilst rigorous and comprehensive Monitoring, Evaluation and Learning (MEL) systems are important without these other elements appropriate adaptation can be hindered. • Adaptive Management requires resources. Where the expected change is complex, adaptation is frequently necessary to ensure we are responding to context and evidence. This should be adequately resourced if we are to expect results. In an environment where many INGOs work consistently within complex environments, the sector also needs more opportunities to trial these approaches and could benefit from more funding streams available which include the kinds of approaches used by DFID in current GEC programming

Monitoring for problem-solving, adaptive management, reporting and learning - Dominique Morel; Dzino-Silajdzic, Velida; Hagens, Clara (Catholic Relief Services, 2020)
Internal and external stakeholders have different information needs over a project’s life, for purposes that include adaptive management, accountability, compliance, reporting and learning. A project’s monitoring, evaluation, accountability and learning, or MEAL, system should provide the information needed by these stakeholders at the level of statistical reliability, detail and timing appropriate to inform data use. In emergency contexts where the situation is still fluid, ‘informal monitoring’ has proved helpful to staff’s ongoing assessment of the broader environment in order to identify changes in the situation, in other actors’ responses, and in priority unmet needs that would require corresponding changes in the response.2 The same distinction between informal monitoring of possible changes in the project’s operating context—whether identified as project assumptions and risk factors or not—and formal monitoring of the activities included in the response and project indicators, is relevant for development contexts too. Informal monitoring: Ongoing assessment of changes in operating context Formal monitoring: Tracking progress against project activities and indicators Within formal monitoring, it is useful to further differentiate between light monitoring and rigorous monitoring: - Light monitoring aims to provide timely feedback on new activities (or new locations or target groups) or aspects of the project’s theory of change (activity-to-output or output-to-IR change) logic that staff are less confident about, to check for early signs that progress is being made and that assumptions are holding true while there is still ample time to make adjustments if necessary.3 - Rigorous monitoring aims to collect representative data for evidence-based project management, reporting and learning, not just at midterm but throughout project implementation.

Adaptation in practice: lessons from teenage pregnancy programmes in Sierra Leone - Castillejo, Clare; Buell, Stephanie (ODI, 2020)
A discussion of initial learning emerging from the SLRC ’Adaptive approaches to reducing teenage pregnancy in Sierra Leone’ action research project.

5 Principles to Guide Adaptive Leadership - Ramalingam, Ben; Nabarro, David; Oqubuy, Arkebe; Carnall, Dame Ruth; Wild, Leni (Harvard Business Review, 2020)
How you respond to a crisis will have repercussions for years to come. The Covid-19 pandemic is constantly evolving, with leaders facing unpredictability, imperfect information, multiple unknowns, and the need to identify responses quickly — all while recognizing the multi-dimensional (health-related, economic, social, political, cultural) nature of the crisis. Responding to the crisis requires adaptive leadership, which involves what we refer to as the 4 A’s: Anticipation of likely future needs, trends and options. Articulation of these needs to build collective understanding and support for action. Adaptation so that there is continuous learning and the adjustment of responses as necessary. Accountability, including maximum transparency in decision-making processes and openness to challenges and feedback.
Keywords: Crisis management; Leadership

USAID Wildlife Asia as a case study in adaptive rigour - Ziegler, Jessica (Briefing Paper, 2020)
This briefing note looks at how the United States Agency for International Development (USAID) Wildlife Asia programme has operationalised the concepts of adaptive rigour and adaptive management as part of its approach to collaborating, learning and adapting. As described by the Global Learning for Adaptive Management (GLAM) initiative, adaptive rigour is about ensuring that the data, information, methods, processes and systems that underpin adaptive management are robust, systematic and high‑quality. Key messages When faced with programmatic complexity, it is important to take an adaptive approach driven by continuous and iterative monitoring, evaluation and learning (MEL). USAID Wildlife Asia, which works to advance regional action towards ending illegal wildlife trafficking in Southeast Asia and China, has embraced this approach as a way of operationalising adaptive rigour. Throughout programming, MEL approaches should reflect the characteristics of adaptive rigour: comprehensiveness, usefulness, practicality, timeliness and support. Utilising performance monitoring and research in order to test and revise technical approaches and employing mixed methods to collect both qualitative and quantitative data, as well as looking for relevant lessons generated by others, can ensure access to the most useful information for decision-making throughout implementation. For adaptive management, it is not enough to monitor, evaluate and learn; it is also essential to pause and reflect in order to analyse and process evidence gained through MEL with colleagues and stakeholders to reach the right conclusions and make good decisions.

Adaptive leadership in the coronavirus response - Ramalingam, Ben; Wild, Leni; Ferrari, Matt (ODI, 2020)
The coronavirus pandemic poses unprecedented challenges to science, policy and the interface between the two. How – and how quickly – policy-makers, practitioners and researchers react to this emerging and complex crisis is making a profound difference to people’s lives and livelihoods (WHO, 2020). But how can we ensure effective collective decision-making on the basis of emerging evidence, changing trends and shifting scientific understanding, all in the face of considerable uncertainty? Recent experience highlights the need for adaptive leadership in national and global responses to the outbreak. This briefing paper sets out key principles for what this might look like, and proposes a roadmap for policy-makers, practitioners and researchers to move towards such an approach as they tackle the unfolding crisis. Key messages Tackling the coronavirus outbreak requires adaptation at operational and leadership levels. Operationally, there is scope to strengthen evidence-based adaptive management practices, to adjust the mix and type of interventions being implemented and learn as we go so as to achieve shared goals. This requires adaptive leadership capacities, being open and transparent about learning, using collective decision-making processes and building trust with communities and individuals.

Navigating adaptive approaches for development programmes - Pett, Jamie (Working Paper, 2020)
This working paper compares six of the most prominent adaptive approaches to emerge over the past two decades. Three come from the world of innovation, largely in the private sector (agile, lean startup and human-centred design), and three from the global development sector (thinking and working politically, forms of adaptive management and problem-driven iterative adaptation). While all of these approaches are valuable when used in the right context, practitioners may be perplexed by the multiplicity of methods and jargon. This paper aims to address some of this confusion by mapping where these approaches have come from and showing how they can be applied across the adaptive programme cycle. Armed with this knowledge, practitioners might experiment with different combinations and sequences of adaptive approaches according to the kind of problem and context faced. In turn, this may help us move beyond a siloed view of approaches linked to innovation, adaptive management or more politically smart ways of working. Key messages: • Adaptive approaches have emerged in several sectors, including software development, product and service design, technology startups and international development. • Adaptive approaches can help practitioners counteract misplaced certainty. By talking to potential users, understanding institutions, interests and ideas and investigating the root causes of a problem, practitioners applying these approaches can illuminate the underlying nature of the problem and context. • Rather than building a whole solution straight away, these approaches commonly encourage practitioners to start small and use structured cycles of testing and learning. There is scope to further consider how different approaches can be better brought together and combined. • Adaptive approaches in development provide a wider range of options for what to create and facilitate – not only products or services, but also forms of collective action. There are also alternative ways to think about scale – considering how others might take up an idea and looking for leverage, rather than quantity.

Mainsreaming gender in an adaptive, politically smart governance programme - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks at the experience of gender mainstreaming in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • When development programmes try to engage with political stakeholders and align with the priorities of wider coalitions there is a danger that gender equality is de-prioritised. • It is important that formal political economy analysis, as well as other data collection, analysis and consultation exercises, are gender-sensitive. Teams should also look for ways to make gendered political and power analysis part of the everyday routine practice of staff. • Working politically and adaptively to advance gender objectives calls for staff with a specific skillset, as well as links to appropriate networks and political stakeholders. It also implies establishing checks and incentives to hold staff and partners accountable for gender objectives, and strong and consistent messaging from team leaders.

Rethinking value for money for adaptive, politically smart programmes - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
- This short paper draws out lessons for working effectively with and through partners, based on the experience of the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Cultivating effective partnerships can be a key part of delivering locally legitimate projects that have the potential to create sustainable change. Adaptive and politically informed ways of working create specific opportunities and challenges for doing this well. • Flexible and adaptive programmes are deliberately designed to experiment and to make small investments in different areas, to see what will work. While this is often important for making headway on complex challenges, it can also leave partners exposed and can undermine trust. • It can also be challenging to balance the need to meet accountability commitments to donors while allowing local partners to take the lead in pursuing their own objectives. • Co-creating plans, priorities and activities with partners has the potential to resolve some of these tensions. But the time and patience required to do this successfully should not be underestimated, and can be difficult to maintain in the face of pressure from donors to see results within a confined timeframe.

Examining the results and adaptation ideas in foreign aid - Janus, Heiner (University of Manchester, 2020)
This thesis applies ideational and institutional theories to analyse how two specific ideas, results and adaptation, have changed the theory and practice of development cooperation. The thesis addresses the question of why the results and adaptation ideas are often treated as binaries and how this debate has evolved historically. In a first theoretical paper, the evolution of results and adaptation is conceptualised as a combination of institutional layering and diffusion within development organisations. The second theoretical paper applies ideational theory, in particular, the coalition magnet framework, to China as a donor country. The empirical papers apply ideational and institutional theories to study aid projects funded by the World Bank and China in the Rwandan agriculture sector. The third paper analyses through which mechanism, results-based principal-agent relationships or problem-driven iterative adaptation, the World Bankâs Program for Results in the agriculture sector in Rwanda has led to increased agricultural productivity. The paper combines causal process tracing and contribution analysis to investigate two underlying theories of change of the Program for Results. The fourth paper applies the same framework and methodology to the Chinese Agricultural Technology Demonstration Center in Rwanda. The fifth paper compares both projects, the World Bank project and the Chinese project. The thesis finds that the ideas of results and adaptation are often presented as mutually exclusive mainly at the general level of public philosophies or paradigms, but show overlap and potential for integration on the level of framing policy problems and policy solutions. The thesis also demonstrates that there is unexplored potential for convergence between China and Development Assistance Committee donors around âcoalition magnetâ ideas. The empirical part of the thesis reveals how results-based and adaptive causal mechanisms co-exist within given aid interventions by the World Bank and China, how these interact and how they ultimately contribute to achieving development outcomes. The key finding is that the broader political context of the Rwandan agricultural sector is the main factor for determining development outcomes, which neither the World Bank project nor the Chinese projects take into account. The comparison of the World Bankâs and Chinaâs interventions finds that donor organisations need to address how results-based ideas in combination adaptive development ideas can be better tailored to fit into the specific context of the Rwandan agriculture sector.

Evidence base for Collaborating, Learning, and Adapting: summary of the literature review (2020 update) - Learning Lab (USAID, 2020)
The LEARN contract and the United States Agency for International Development/Bureau of Policy, Planning, and Learning (USAID/PPL) are managing an area of work known as the Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer the following key learning questions: ● Does an intentional, systematic, and resourced approach to collaborating, learning, and adapting (CLA) contribute to organizational effectiveness and/or development outcomes? ● If so, how? And under what conditions? ● How do we know? How do we measure any contribution that CLA makes to development results? As we began this work, we identified the need to conduct a literature review looking at these questions to understand what is known, what remains unknown, and how others have tried to answer these questions to date. We were primarily interested in answering these questions: ● What evidence is there, if any, that collaborating, learning, and/or adapting contributes to organizational effectiveness, development outcomes, or both? What are the strongest pieces of evidence? ● Does the literature identify any factors critical to CLA that are not currently included in the CLA framework? ● Who else is working on measuring the impact of collaborating, learning and adapting? ● What methods and measures did researchers use to study the effects of collaborating, learning, and adapting? ● Where are there gaps in the research relevant to collaborating, learning, and adapting? ● When taken together, what practical guidance does the evidence for collaborating, learning, and adapting offer to practitioners and policy makers to improve organizational effectiveness and development outcomes?

Working effectively through partnerships - Lessons from Institutions for Inclusive Development in Tanzania - Laws, Ed (ODI, 2020)
• This paper looks critically at the approach to value for money (VfM) in the Institutions for Inclusive Development (I4ID) programme – an adaptive, politically smart governance programme in Tanzania. • Adaptive, politically smart programmes like I4ID aim to deliver VfM by learning about what will work in complex environments, and quickly incorporating those lessons into delivery. When functioning properly, they can rapidly wind down activities as new information emerges and divert funding to more effective alternatives. • This means that adaptive programmes will achieve their potential to deliver strong VfM when their processes are good – when appraisal of experimental efforts is timely, consistent, knowledgeable and politically astute. As these programmes mature in their implementation phase, VfM evaluation should be focused on checking for a culture of adaptation and learning supported by strong adaptive processes. • While economy is important for adaptive programmes, it is also important that keeping costs low does not deprive teams of the resources, staff, and management and administration time they need to gather information, experiment, learn and adapt.

AdaptScan - Improving your Team's Adaptive Management - Mercy Corps (Mercy Corps, 2020)

Principles for managing in complexity - Proud, Emma (LearnAdapt, 2020)
Written by Toby Lowe and Shaheen Warren (Centre for Public Impact) and Sam Sharp (Overseas Development Institute), with input from Jamie…

A New Policy Narrative for Pastoralism? Pastoralists as Reliability Professionals and Pastoralist Systems as Infrastructure - Roe, Emery (ESRC STEPS Centre, 2020)
This paper proposes that pastoralist systems are better treated, in aggregate, as a global critical infrastructure. The policy and management implications that follow are significant and differ importantly from current pastoralist policies and recommendations. A multi-typology framework is presented, identifying the conditions under which pastoralists can be considered real-time reliability professionals in systems with mandates preventing or otherwise avoiding key events from happening. The framework leads to a different policy-relevant counternarrative to pastoralism as understood today. Some features of the counternarrative are already known or have been researched. The paper’s aim is to provoke further work (including case research and interactions with decisionmakers) on how robust the counternarrative is as a policy narrative for recasting today’s pastoralist policy and management interventions.

What difference does CLA make to development? Key findings from a recent literature review (2020 update) - Learning Lab (USAID, 2020)
USAID’s Bureau for Policy, Planning and Learning and its LEARN support contract are working to integrate systematic, intentional and resourced collaborating, learning and adapting (CLA) throughout program planning and implementation to achieve more effective development programs. As part of this effort, USAID is exploring several approaches to understand whether and how strategic collaboration, continuous learning and adaptive management make a difference to organizational effectiveness and development outcomes. To begin this work, we have undertaken a foundational literature review of academic and gray literature to answer our key learning questions: • Does an intentional, systematic and resourced approach to collaborating, learning and adapting contribute to organizational effectiveness? To development outcomes? • If so, how? And under what circumstances? • How do we measure the contribution? The 13 key findings, mapped to the CLA Framework below, are described in greater detail in the following pages.

Uncertainty and COVID-19: A turning point for Monitoring Evaluation, Research and Learning? - A discussion note for aid actors, policymakers and practitioners - Tyrrel, Lavinia; Roche, Chris; Jackson, Elisabeth (Abt Associates, 2020)
The COVID-19 pandemic has significantly shifted the context in which aid and development is being delivered. The global scale of the pandemic and the speed at which it is spreading mean that the ‘normal’ economic, ideological and organisational influences which shape (if not determine) aid delivery are in flux. This means that – for a relatively short-period – there is scope for aid actors to work collectively to embed more locally-led, politically-informed and adaptive forms of MERL in aid and development practice. These forms of Monitoring Evaluation Research and Learning (MERL) are not only well-suited to the current global pandemic. They also offer ways for aid program decision makers and practitioners to make sense of the complex and uncertain contexts in which much development work takes place. Applying locally-led, politically-informed and adaptive forms of MERL in the COVID-19 context and beyond requires a shift in mindset and approaches. Situations of complexity, in which it is difficult to predict the relationships between cause and effect, do not lend themselves to linear approaches and fixed indicators. Instead, they require ‘navigation by judgement’, ongoing learning and adaptation and greater privileging of local knowledge, and of the perspectives of those who are often excluded. Rather than being focused on upwards accountability, simple numbers and good news stories, the core function of MERL in this context is to support a better understanding – in real-time – of the changing operating context, to generate learning about the immediate impact of policy and program responses and their longer-term effects, and to inform decision making by front line staff. Whether the opportunities afforded by this ‘critical juncture’ are realised will depend on the degree to which those in the aid and development sector use this opportunity to promote a shift in the deep incentive structures within which development agencies are embedded. On the one hand, the pandemic underscores the limits of the linear understandings of change which underpin many orthodox approaches to planning, design and associated MERL. On the other hand, there is a vested interest in the status quo amongst many organisations, consultants, researchers and MERL practitioners. This is because approaches which promote locally-led development inevitably require those in power to relinquish control. While a range of factors make this shift difficult, there is more scope to change internal ways of working in development agencies than is commonly acknowledged. There is no time like the present to advocate for a ‘new normal’ for MERL.

Diseño transformacional de proyectos - Kehrer, Daniel (GIZ, 2020)
There are many definitions of the term ‘transformation’ or ‘transformational change’. The first section of the report develops a basic understanding of transformations or transitions (used synonymously) viewed from various perspectives. In this, transformations are defined as processes that use disruptive innovations to change systems into fundamentally new systems that subsequently form the new mainstream. Section two describes existing approaches to environmental and climate finance in international cooperation and discusses them in light of the proposed definition. All of the approaches have the potential to be further refined and in that process often to increase the precision of what is understood by each type of transformation. The definitions already state which criteria and indicators are referred to and how relevant they are. There is wide diversity in the type of criteria and indicators used by the various organisations, and how they are classified, but certain common features can be identified and with the aid of the literature on transformations they can be combined to form a comprehensive framework. With this in mind, the derivation of quality criteria for transformative interventions is explained in section 3.1. Transformational change at one and the same time calls for big decisions and innumerable projects in a particular field of transformation; the projects cannot be planned on the drawing board but still should be coordinated with each other. Section 3.2 offers guidance on this. Section 3.3 argues in favour of focusing more closely on the ‘process promise’ and employing a more iterative and more adaptable commissioning procedure. Finally, section 3.4 introduces two types of indicators under the various criteria: design indicators, which measure the quality of interventions that are aimed at influencing transformations (process orientation), and outcome indicators, which measure the process and/or progress of a transformation itself.

Transformative project design - Kehrer, Daniel (GIZ, 2020)
There are many definitions of the term ‘transformation’ or ‘transformational change’. The first section of the report develops a basic understanding of transformations or transitions (used synonymously) viewed from various perspectives. In this, transformations are defined as processes that use disruptive innovations to change systems into fundamentally new systems that subsequently form the new mainstream. Section two describes existing approaches to environmental and climate finance in international cooperation and discusses them in light of the proposed definition. All of the approaches have the potential to be further refined and in that process often to increase the precision of what is understood by each type of transformation. The definitions already state which criteria and indicators are referred to and how relevant they are. There is wide diversity in the type of criteria and indicators used by the various organisations, and how they are classified, but certain common features can be identified and with the aid of the literature on transformations they can be combined to form a comprehensive framework. With this in mind, the derivation of quality criteria for transformative interventions is explained in section 3.1. Transformational change at one and the same time calls for big decisions and innumerable projects in a particular field of transformation; the projects cannot be planned on the drawing board but still should be coordinated with each other. Section 3.2 offers guidance on this. Section 3.3 argues in favour of focusing more closely on the ‘process promise’ and employing a more iterative and more adaptable commissioning procedure. Finally, section 3.4 introduces two types of indicators under the various criteria: design indicators, which measure the quality of interventions that are aimed at influencing transformations (process orientation), and outcome indicators, which measure the process and/or progress of a transformation itself.

LEARN End of Contract Report - Learning Lab (USAID, 2020)
In September of 2014, USAID’s Office of Learning, Evaluation & Research (LER) awarded the Learning and Knowledge Management (LEARN) contract to Dexis Consulting Group and subcontractor RTI International.1 This document—the End of Contract Report—captures five and half years of results and reflections for our stakeholders. Our intention is to share the good and the bad, and while this report would not be considered a “tell all,” we think we have a story worth sharing, particularly to USAID CORs and AORs, activity managers, and other implementers of institutional support contracts.2 LEARN’s primary purpose was to support organizational change at USAID. More specifically, the contract was focused on helping USAID staff integrate collaborating, learning, and adapting (CLA) approaches into the design, implementation, monitoring, and evaluation of programs (what is known at USAID as the Program Cycle). It was clear that most USAID staff, whether they realized it or not, were already integrating CLA into their work to some extent. The focus of our efforts, therefore, was to make those practices more systematic, intentional, resourced, and ultimately more widespread throughout the Agency, which would have a ripple effect on implementing partners and even other stakeholders, such as host country governments. This was based on the theory—later borne out by evidence—that by becoming a better learning organization, USAID could be a more effective development organization. And that theory brought the USAID CLA team within USAID’s Bureau for Policy, Planning & Learning (PPL) and LEARN contractors together, driven by a shared purpose of improving how USAID does business. LEARN was designed based on this belief and, as you might expect from a learning-oriented contract, began with more questions than answers. Primary among those questions was: could an institutional support contract do more than carry out requested services—could it actually accelerate positive organizational change at USAID? And if so, how and under what conditions?

Smart Implementation of complex change processes - Beier, Christoph; Kirsch, Renate (Global Solutions Journal, 2020)
Cooperation management facilitates the recoupling of progress toward sustainable development

Crisis relief for adults & families everywhere - Featuring the mighty micro-VCoL - Lectica (Lectica Live, 2020)
In response to the COVID-19 pandemic and the resulting economic crisis, we're open-sourcing our most effective stress- and crisis-management learning tools. We call these tools micro-VCoLs™. All of the micro-VCoLs shared here can be practiced effectively just by following the instructions.

Learning From Failure 2020 - What CARE’s evaluations tell us about how to improve our work - CARE (CARE, 2020)
“Ever failed. No matter. Try again. Fail again. Fail better.” --Samuel Beckett Here’s my favorite part of that quote: the ultimate goal is not a lack of failure; it’s better failures. That’s good news for CARE, because we just published round two of our Learning From Failure initiative, and…I know this will surprise everyone…we haven’t stopped failures yet. We do have some hopeful signs that we’re failing better; or at least, that we’re improving on some concrete weaknesses we identified in the first round. It’s an interesting process to launch the second phase of learning from failure. The first round, we didn’t know what we were going to find. We spent as much time talking about how it was the first-ever report of its kind as we did about the actual failures. Our case study admitted, “It's still very early to see specific development impacts.” Round two isn’t quite the same. It’s not new anymore, so there’s less excitement at having invented something. We’re not discovering data and themes for the first time. In a lot of ways, the stakes are higher. Round two of learning from failure becomes an exercise in continuous performance improvement, rather than a journey of discovery. If we don’t see improvements, we don’t have the excuse that it’s too early to tell. It also takes a sustained commitment. Launching an exploratory exercise at a small scale is easy, especially when no one quite knows what the answers will be. Pulling together a few pieces of content over a few months is pretty straightforward. It takes some staying power—and real support from leadership—to keep up the work over time, especially in the middle of a pandemic. That’s even more true once we’ve seen one round of results and had a chance to understand the work that it takes to improve.

Transforming our work: Getting ready for transformational projects - Kehrer, Daniel; Flossmann-Kraus, Ursula; Ronco Alarcon, Sabrina Valeria; Albers, Vivien; Aschmann, Gwendolin (GIZ, 2020)

SystemCraft - a primer: How to Tackle our Toughest Problems - Simpson, Kate; Randall, Ian (Wasafiri, 2020)
Systemcraft is our applied framework to help leaders and organisations get started and keep going when faced with complex problems. It is built on our practical experience. It draws on a broad body of research, action and theory from the worlds of complexity thinking, systems theory, adaptive management, leadership development, social movements, development theory and beyond. Systemcraft has been designed to make systems thinking something any leader can apply when they find themselves faced with a complex problem and asking, ‘So what do I do next?’

Thinking and Working Politically in development - Coalitions for Change in The Philippines - Sidel, John T.; Faustino, Jaime (The Asia Foundation, 2020)
The Asia Foundation and the Australian Embassy in the Philippines today released a new publication, Thinking and Working Politically in Development: Coalitions for Change in the Philippines. Written by London School of Economics and Political Science Professor John T. Sidel and The Asia Foundation’s Jaime Faustino, the book examines the first phase of the Coalitions for Change program (2012-2018) and the contributions to key development policy reforms in the Philippines. The book is a rigorous treatment of the Coalitions for Change program’s transformative policy reforms—alongside lessons from its failures—across diverse policy arenas and in a wide variety of cities and provinces. The chapters are organized thematically: excise tax reform (Chapter 2), land governance reform (Chapter 3), education (Chapter 4), electoral reform (Chapter 5), disaster risk reduction and management (Chapter 6), and subnational governance reform and conflict resolution in Mindanao (Chapter 7). The co-authors together combine an independent, academic perspective on the program’s impacts (Sidel) with a front-row view of doing policy reform in the Philippines – both its political and technical dimensions (Faustino). Based on the empirical research and comparative analysis undertaken by the authors, the book articulates – and substantiates – a strong set of arguments that help to explain the program’s mixed pattern of achievements and disappointments. Overall, the book concludes that the seven-year program achieved significant and sustainable impact using problem-driven, adaptive, and iterative approaches to developmental change. The authors assert the program was at the forefront of notable development approaches: aid effectiveness and development around thinking and working politically, doing development differently, and adaptive programming. Graham Teskey, an early advocate of ‘thinking and working politically’ explores how development agencies can replicate the conditions for success in his Afterword. With illustrative case studies and analyses, the book provides valuable lessons for policymakers, scholars, bilateral agencies, think-tanks, and anyone interested in successfully maneuvering the shifting dimensions of development in the Philippines and elsewhere.

A Pragmatic Approach to Assessing System Change - Posthumus, Hans; Shah, Rachel; Miehlbradt, Alexandra; Kessler, Adam (DCED, 2020)
Planning for and assessing system change is a strategic management issue. It is critical for everything from developing a strategy and designing interventions, to adapting strategy, improving implementation and reporting impact. But many programmes get stuck when it comes to assessing system change. The private sector development field has struggled to agree on an approach that programmes can implement and stakeholders can understand. However some mature programmes are starting to assess system change more effectively. Building on these emerging practices, this paper outlines a process that programmes can use to assess system changes regularly and practically. Two complementary papers: Overview and How to put it into practice The Overview summarises the approach and How to put it into practice provides more detailed implementation guidance, worked examples, and useful tips. The Overview explores how to: develop a system change strategy and intervention plans that lay the groundwork for system change assessment, including how to set system boundaries and how to identify the system changes a programme aims to catalyse assess system changes using both: - an intervention lens focused on changes introduced by specific interventions - a helicopter lens that provides a whole system view By analysing findings from both lenses, programmes can improve their strategy and report on their contribution to system change. How to put it into practice uses two case examples for illustration throughout the paper - PRISMA’s work in the maize system in East Java and Indonesia and S4J’s work in the Vocational Education and Training (VET) system in Albania. It targets practitioners responsible for facilitating and/or assessing system change. The paper explains how to: articulate the system changes that a programme aims to catalyse assess those changes use the results to inform decision making and reporting The approach described in the paper builds on the practices outlined in the DCED Results Measurement Standard. The guidance provided has been designed to be useful to programmes that aim to catalyse system changes whether or not they apply the DCED Standard.

A Pragmatic Approach to Assessing System Change: How to put it into practice - Miehlbradt, Alexandra; Shah, Rachel; Posthumus, Hans; Kessler, Adam (DCED, 2020)
Planning for and assessing system change is a strategic management issue. It is critical for everything from developing a strategy and designing interventions, to adapting strategy, improving implementation and reporting impact. But many programmes get stuck when it comes to assessing system change. The private sector development field has struggled to agree on an approach that programmes can implement and stakeholders can understand. However some mature programmes are starting to assess system change more effectively. Building on these emerging practices, this paper outlines a process that programmes can use to assess system changes regularly and practically. Two complementary papers: Overview and How to put it into practice The Overview summarises the approach and How to put it into practice provides more detailed implementation guidance, worked examples, and useful tips. The Overview explores how to: develop a system change strategy and intervention plans that lay the groundwork for system change assessment, including how to set system boundaries and how to identify the system changes a programme aims to catalyse assess system changes using both: - an intervention lens focused on changes introduced by specific interventions - a helicopter lens that provides a whole system view By analysing findings from both lenses, programmes can improve their strategy and report on their contribution to system change. How to put it into practice uses two case examples for illustration throughout the paper - PRISMA’s work in the maize system in East Java and Indonesia and S4J’s work in the Vocational Education and Training (VET) system in Albania. It targets practitioners responsible for facilitating and/or assessing system change. The paper explains how to: articulate the system changes that a programme aims to catalyse assess those changes use the results to inform decision making and reporting The approach described in the paper builds on the practices outlined in the DCED Results Measurement Standard. The guidance provided has been designed to be useful to programmes that aim to catalyse system changes whether or not they apply the DCED Standard.

System Innovation Network - Si Network (Si Network, 2020)
The Si Network is an online platform for building the developing of systems innovation - connecting people around the world to learn and apply the ideas and methods of systems innovation towards addressing complex challenges and building better systems that work for all. Not sure what systems innovation is? Systems innovation is a new approach to innovation that tries to tackle complex social and environmental challenges through the use of more holistic & innovation driven approaches. It is a kind of innovation that aims to change the underlying structure of a system, thus potentially enabling a more transformational kind of change - systems change - rather than incremental "innovation as usual". What Do You Do? We are building an ecosystem of individuals and organizations co-learning and co-creating systems innovation across geographies and sectors. This ecosystem is enabled by our online platform which provides educational content, toolkits, organizes events and projects as well as provides various support services for organizations. Purpose Statement Our purpose is to build the world’s capacity for systems innovation - so as to better understand and address complex challenges and co-create a world where systems work for all. We envision a world where everyone thinks in systems and has an understanding of complex systems. From this understanding, we are able to design and develop regenerative systems that work for everyone. Our mission is to grow the field of systems innovation as a pathway to co-learn the ideas of systems thinking and apply them to co-creating new systems Who's Involved? We are a networked organization of some 17K+ members forming part of 20+ hubs in major cities around the world. Our community is broad and diverse in areas of work and interest from designers, innovators, and entrepreneurs, to researchers and management but they all share a common interest in learning and applying systems thinking ideas. The Si platform is developed and managed by a small core team based in London UK. We are registered as a business but operate as a social enterprise focused on our purpose of advancing the area of systems innovation in theory and practice. Core Value Creativity - We put creativity at the centre of what we do. Holding a space for curiosity, diversity of views, exploration and critical thinking as a pathway to transformative innovation. Openness - We strongly believe in openness in our ways of being, thinking and organizing as a sustainable pathway to creating an adaptive, scalable and dynamic community. Growth Mindset - We embrace challenges as opportunities for continuous personal and collective learning and development, with a never-ending potential to grow and start with a new beginning. Perseverance - When facing uncertainty and failure, perseverance is what is needed to maintain commitment and a resilient pathway aligned with our purpose. Care - Care is one of our core principles. We foster relationships based on honesty and empathy, striving to be present and conscious in what we do and taking responsibility for the effects of our actions.